DOI: 10.31274/rtd-180813-12426
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical characterization of ultrasonic NDE systems

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…The damping setting, which should not affect the receiver characteristics in this pitch-catch setup, was set at 0. In general, these results and the results similarly obtained with 5-and 10-MHz transducers (see [3]) showed that:…”
Section: Receiver Characterizationsupporting
confidence: 77%
See 4 more Smart Citations
“…The damping setting, which should not affect the receiver characteristics in this pitch-catch setup, was set at 0. In general, these results and the results similarly obtained with 5-and 10-MHz transducers (see [3]) showed that:…”
Section: Receiver Characterizationsupporting
confidence: 77%
“…Figures 7 and 8 show the measured Thevenin equivalent sources and impedances for energy settings 2 and 4 (and damping settings of 0, 5, and 10). Dang, in his thesis [3], also gave the corresponding results for energy settings 1 and 3, which behave similarly to those shown. The left column in each figure shows the magnitude of source strength and right column shows the corresponding magnitude of the internal electrical impedances measured by using the three external impedances.…”
Section: Pulser Characterizationsupporting
confidence: 70%
See 3 more Smart Citations